Pierwsza księga o poznańskim Czerwcu. Źródła legendy - Fiećko, Jerzy (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The author describes the origin of the first remembrance book devoted to Poznań 1956 protests, edited by Jarosław Maciejewski and Zofia Trojanowiczowa, professors of Polish at Adam Mickiewicz University in Poznań, and published during the “Solidarity carnival” of 1981. The essay describes attempts by those in power to stall the initiative, presents and comments on the content of the book, which was regarded by many readers as the “book of the year”. The essay also makes a number of statements on the reasons for the book’s success and its instantly legendary status.